THEORETICAL AND EMPIRICAL INSIGHTS INTO EMOTIONAL INTELLIGENCE IN MODERN PSYCHOLOGICAL RESEARCH - Salikhova Zukhra Mirkhosil qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article provides a comprehensive theoretical and empirical analysis of emotional intelligence within modern psychological research. The study examines key conceptual approaches, including the ability model, mixed models, and trait-based perspectives. Particular attention is given to the structural components of emotional intelligence such as emotional awareness, regulation, empathy, and social competence. The findings demonstrate that emotional intelligence plays a crucial role in personality development, social adaptation, educational effectiveness, and professional performance. The paper also emphasizes that emotional intelligence is not a fixed trait but a dynamic and developable capacity that can be enhanced through psychological and pedagogical interventions.